2016
DOI: 10.1016/j.ebiom.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

H19 Noncoding RNA, an Independent Prognostic Factor, Regulates Essential Rb-E2F and CDK8-β-Catenin Signaling in Colorectal Cancer

Abstract: HighlightsHigh H19 expression in primary tumors is an independent predictor of short overall survival in CRC patients.RB1-E2F and CDK8-β-catenin signaling are essential in mediating the oncogenic activity of H19 in CRC.Combined analysis of H19 and its targets further improved the prediction power on overall survival of CRC patients.Long noncoding RNAs (lncRNAs) are transcripts at least 200 nucleotides long that do not code for proteins. The clinical relevance of lncRNAs in colorectal cancer (CRC) is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 55 publications
(76 reference statements)
2
103
0
Order By: Relevance
“…Thus, as a part of the transcription machinery, CDK8 plays a crucial role in regulating gene expression. Accordingly, the findings by Calin and coworkers (Ohtsuka et al, in this issue) show, that apart from the detection of the H19 action on CDK8/β-catenin, as well as on RB1/E2F signaling, H19 may be involved in further regulation networks that control CRC malignancies.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, as a part of the transcription machinery, CDK8 plays a crucial role in regulating gene expression. Accordingly, the findings by Calin and coworkers (Ohtsuka et al, in this issue) show, that apart from the detection of the H19 action on CDK8/β-catenin, as well as on RB1/E2F signaling, H19 may be involved in further regulation networks that control CRC malignancies.…”
mentioning
confidence: 99%
“…In this case, the data emphasize that H19 functions are performed by miR-675. However, Calin and coworkers (Ohtsuka et al, in this issue) found a direct interaction of H19, without the involvement of miR-675, with RB1 protein, using RNA immunoprecipitation experiments. This excellent study also showed that H19 silencing dramatically reduced RB1 phosphorylation by reducing both RNA and protein expression of cyclin-dependent kinase (CDK) 4 and cyclin D1 (two essential upstream factors controlling RB1 phosphorylation).…”
mentioning
confidence: 99%
See 3 more Smart Citations